Konflik Budaya Dalam Konstruksi Kecantikan Wanita Indonesia (Analisis Semiotika Dan Marxist Iklan Pond’s White Beauty Versi Gita Gutawa) - Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2015)
AbstractThis study will explore the cultural conflict that is displayed in the advertisements Pond's White Beauty Gita version Velasquez with pretty white theme flushed like korea. Where this ad makes the construction of beauty in women Indonesia becomes opaque, just for the sake of following the trend that there are women in Indonesia made into a false consciousness of the concept of beauty. This research was conducted by using the method of semiotic analysis and Marxist analysis. The conclusion that can be derived from these studies is advertising Pond's creates a cultural conflict in terms of the meaning of beauty for women in Indonesia. Semiotic analysis shows that advertising Pond's White Beauty featuring stereotypes about the picture of beauty for women in Indonesia. Beautiful woman is a white female Korean people while for the people of Indonesia who have different genetic, it is becoming a benchmark that can not be equated. Pond's ad showing false consciousness, in which Indonesian women can have white skin like Korea only by using Pond's products. Based on Marxist analysis can be seen that ad Pond's is made for the benefit of the capitalists, which in this case is the product manufacturer Unilever. Unilever as capitalist menghegomoni Indonesian women to buy Pond's beauty products using advertising media to create false consciousness in the minds of Indonesian women about the picture of beauty.AbstrakPenelitian ini akan menggali konflik budaya yang ditampilkan dalam iklan Pond’s White Beauty versi Gita Gutawa dengan tema cantik putih merona seperti korea. Dimana iklan ini menjadikan konstruksi kecantikan pada wanita Indonesia menjadi buram, hanya demi mengikuti trend yang ada wanita di Indonesia dibuat menjadi memiliki kesadaran palsu akan konsep kecantikan. Penelitian ini dilakukan dengan menggunakan metode analisis semiotik dan juga analisis Marxist. Kesimpulan yang dapat diperoleh dari studi ini adalah iklan Pond’s menciptakan konflik budaya dalam hal makna kecantikan bagi perempuan Indonesia. Analisis semiotik menunjukkan bahwa iklan Pond’s White Beauty menampilkan stereotip mengenai gambaran kecantikan bagi perempuan Indonesia. Perempuan yang cantik merupakan perempuan yang putih seperti orang Korea padahal bagi orang Indonesia yang memiliki genetik berbeda, hal ini menjadi tolak ukur yang tidak dapat disamakan. Iklan Pond’s ini menampilkan kesadaran palsu, dimana perempuan Indonesia dapat memiliki kulit putih seperti Korea hanya dengan menggunakan produk Pond’s. Unilever sebagai kapitalis menghegomoni para perempuan Indonesia untuk membeli produk kecantikan Pond’s dengan menggunakan media iklan untuk menciptakan kesadaran palsu dalam pikiran para perempuan Indonesia tentang gambaran kecantikan.